Perbedaan Hasil Belajar Teknik Penulisan Karya Ilmiah Antara Mahasiswa Yang Dibelajarkan Menggunakan Metode Drill and Practice Dengan Metode Tutorial - Padlurrahman, Padlurrahman (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2019)
This study aims to know the difference on learning outcome of scientific writing paper technique between student who is taught by using drill and practice method with tutorial method study program of Indonesian Language and Literature Education at Faculty of Teacher Training and Education Hamzanwadi University.This study was comparative by using the experimental method with the quasy experiment design. This study sample was the fourth semester for student of Study Program of Indonesian Language and Literature Education at Hamzanwadi University.The data was collected by using test technique and analyzed using the ttest. the result of the analysis of variance showed that tcount 4.60> ttable = 1.68 at the significance level of 95% so that there was difference in the result of learning scientific writing paper technique of student who was taught by using drill and practice method with the tutorial method. Furthermore, if it is viewed from the average obtained, the learning outcome of student's scientific writing paper technique is taught by using a drill and practice method higher than the tutorial method.Keywords : learning outcome; drill and practice method; tutorial method.